2018
DOI: 10.1021/acs.cgd.8b00483
|View full text |Cite
|
Sign up to set email alerts
|

Low Pressure Chemical Vapor Deposition Growth of Wide Bandgap Semiconductor In2O3 Films

Abstract: Wide-bandgap semiconductor indium sesquioxide (In2O3) thin films were grown on yttria-stabilized-zirconia (YSZ) substrates with (100), (110), and (111) orientations using a previously unexplored growth method: low pressure chemical vapor deposition. High purity metallic indium (In) and oxygen (O2) were used as precursors, and argon (Ar) was used as the carrier gas. The growth condition was optimized to balance the precursor vapor pressure and the suppression of the gas phase reaction to facilitate the growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…18,19 With the In 2 O 3 buffer layer, the subsequent growth of single crystalline Sn-doped Ga 2 O 3 was stabilized in the pure κ-phase, and the only observed diffraction peak at 38.80°corresponds to the κ-Ga 2 O 3 (004) plane. 11,20 As a result, the out-of-plane relationship is κ- The diffraction pattern for the κ-Ga 2 O 3 (102) plane exhibits a six-fold symmetry, which is resulted from the (001)-oriented κ-Ga 2 O 3 orthorhombic rotational domains formed on (111)-oriented cubic substrates with a relative azimuth of 120°, consistent with reported κ-Ga 2 O 3 on NiO 21 and ITO. 22 Consequently, the in-plane epitaxial relationship between the epilayer and the substrate is…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…18,19 With the In 2 O 3 buffer layer, the subsequent growth of single crystalline Sn-doped Ga 2 O 3 was stabilized in the pure κ-phase, and the only observed diffraction peak at 38.80°corresponds to the κ-Ga 2 O 3 (004) plane. 11,20 As a result, the out-of-plane relationship is κ- The diffraction pattern for the κ-Ga 2 O 3 (102) plane exhibits a six-fold symmetry, which is resulted from the (001)-oriented κ-Ga 2 O 3 orthorhombic rotational domains formed on (111)-oriented cubic substrates with a relative azimuth of 120°, consistent with reported κ-Ga 2 O 3 on NiO 21 and ITO. 22 Consequently, the in-plane epitaxial relationship between the epilayer and the substrate is…”
Section: Resultssupporting
confidence: 82%
“…For the Ga 2 O 3 layer directly grown on YSZ (111), no diffraction peaks corresponding to Ga 2 O 3 were observed, indicative of its amorphous state. In comparison, the pure-phase cubic-structured In 2 O 3 epitaxial layers were grown on the YSZ (111) substrate owing to its thermodynamically most stable termination and the lowest energy cleavage plane, as evidenced by the dominant diffraction peak at 30.52°. , With the In 2 O 3 buffer layer, the subsequent growth of single crystalline Sn-doped Ga 2 O 3 was stabilized in the pure κ-phase, and the only observed diffraction peak at 38.80° corresponds to the κ-Ga 2 O 3 (004) plane. , As a result, the out-of-plane relationship is κ-Ga 2 O 3 [004]//In 2 O 3 [222]//YSZ [111]. Figure b shows the XRD Φ-scan patterns of cubic-In 2 O 3 (044) and orthorhombic κ-Ga 2 O 3 (102).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Most existing works study thin film samples and as a result, most of the applications are designed around thin film samples as well. 22 Bierwagen and Speck reported high quality thin films grown by plasmaassisted molecular beam epitaxy (PAMBE); 4,23 Yang et al reported similarly high quality thin films grown by metal organic vapor phase epitaxy; 24 and Karim, Feng, and Zhao reported high quality thin films grown by low pressure chemical vapor deposition, 25 for example. Recently, Galazka et al developed a high quality single crystal bulk growth method, and thereby provided substrates with large surface areas for epitaxy.…”
Section: Introductionmentioning
confidence: 99%
“…Most existing works study thin film samples and as a result, most of the applications are designed around thin film samples as well. 22 Bierwagen and Speck reported high quality thin films grown by plasmaassisted molecular beam epitaxy (PAMBE); 4,23 Yang et al reported similarly high quality thin films grown by metal organic vapor phase epitaxy; 24 and Karim, Feng, and Zhao reported high quality thin films grown by low pressure chemical vapor deposition, 25 for example. Recently, Galazka et al developed a high quality single crystal bulk growth method, and thereby provided substrates with large surface areas for epitaxy.…”
Section: Introductionmentioning
confidence: 99%